Redescription of two species of Capillogryllus Xie, Zheng & Liang, 2003, with a new species from China (Orthoptera: Gryllidae; Gryllinae) - Wu, Qian; Ma, Li-Bin (Zootaxa, 2023)
The species with a strongly pubescent body with the genus name Capillogryllus by Xie, Zheng, and Liang in 2003 are reviewed. Capillogryllus has presently two species, Capillogryllus exilipalpis Xie & Zheng, 2003 (type specimen is a female), and Capillogryllus dolabripalpis Xie & Zheng, 2003 (type species), both of which are only known from China at this time. In Gyirong County, Tibet, we discovered a new species of this genus that is distinct from the two species mentioned above. Here, three species of Capillogryllus are described and illustrated.